(untitled) (Indian Journal of Integrative Medicine, 2024)
Background: Healthy, youthful skin has a significant impact on confidence and self-esteem. The oil-to-water ratio is crucial for achieving radiant skin, but factors such as aging, lifestyle, and environmental influences can disrupt this balance, resulting in dullness and premature aging. As a result, many individuals seek natural, non-invasive treatments such as cosmetic acupuncture, which, despite its roots in traditional Chinese medicine, lacks substantial scientific validation. This study explores the potential of cosmetic acupuncture to enhance facial aesthetics. Aims and Objectives: This study evaluates the effectiveness of cosmetic acupuncture on facial skin hydration and oil content in women aged 20–35. The primary objective is to measure changes in skin water and oil content using a Facial Skin Analyzer. Secondary objectives include evaluating subjective improvements in skin appearance using the Patient’s Aesthetic Improvement Scale (PAIS) and the Global Aesthetic Improvement Scale (GAIS). Methods: Sixty women from the International Institute of Yoga and Naturopathy Medical Sciences, Chengalpattu, were randomly assigned to either the Facial Cosmetic Acupuncture (FCA) group and control group (n=30). The FCA group 30-minute treatments twice a week, while the control group did not receive any intervention. Measurements were taken at baseline, weekly during the intervention, and four weeks post-intervention. Results: The FCA group showed significant improvements in skin hydration compared to the control group, with more water and less oil content. Treatment efficacy varies with age. Subjective assessments using PAIS and GAIS confirmed these findings, with participants show moderate to significant improvements in their skin appearance. Discussion: Cosmetic acupuncture effectively enhances skin moisture and balance. Potential mechanisms include increased collagen synthesis, vasopressin modulation, improved lymphatic drainage, and aquaporin-3 activation. The combination of empirical data and subjective assessments provide a comprehensive analysis of FCA’s impact on skin health. Conclusion: FCA is non-invasive method for improving skin hydration and oil balance. This study emphasizes the need for further research to investigate long-term effects and optimize treatment protocols, while supporting FCA as a viable cosmetic therapy. Given the growing interest in non-invasive cosmetic procedures, these findings are pivotal for promoting skin health and well-being.